2016
DOI: 10.1515/logos-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing temporal changes in chemical composition of biogenic deposits in the middle Tążyna River Valley (Kuyavian Lakeland, central Poland)

Abstract: The present paper discusses the influence of geochemical properties on biogenic deposits in the Wilkostowo mire near Toruń, central Poland. The analysed core has allowed the documentation of environmental changes between the older part of the Atlantic Period and the present day (probably interrupted at the turn of the Meso-and Neoholocene). In order to reconstruct the main stages in the sedimentation of biogenic deposits, we have used stratigraphic variability of selected litho-geochemical elements (organic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…2) In the organic soils content of P and K is related with organic matter and mineral composition of minerals. Generally content of these elements increased with progress of mursh-forming process and degree of organic matter decomposition (Dobrowolski et al, 2010;Okupny et al, 2016). Studied organogenic soils developed on carbonate sediments are characterised low P and K content due to the properties of the organogenic layers and the subsoil containing small amounts of minerals that are their main source.…”
Section: Chemical Properties Of Organogenic Layersmentioning
confidence: 99%
See 2 more Smart Citations
“…2) In the organic soils content of P and K is related with organic matter and mineral composition of minerals. Generally content of these elements increased with progress of mursh-forming process and degree of organic matter decomposition (Dobrowolski et al, 2010;Okupny et al, 2016). Studied organogenic soils developed on carbonate sediments are characterised low P and K content due to the properties of the organogenic layers and the subsoil containing small amounts of minerals that are their main source.…”
Section: Chemical Properties Of Organogenic Layersmentioning
confidence: 99%
“…This element, similarly to Ca and Mg, is easily leached from rocks that build the catchment and it gets into the lakes with flowing water creating limnic deposits or entering their composition (Kelts and Hsü, 1978). The content of Mg and Na in the carbonate sediments should be mainly associated with allogenic mineral material (Dobrowolski et al, 2010;Okupny et al, 2016). Among the analysed macronutrients, statistical analysis showed that significant differences occur in the case of C, N and Mg contents between peat and mursh layers and other inorganic soils.…”
Section: Chemical Properties Of Organogenic Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Cal car e ous de pos its, con sid ered as in di cat ing a hy dro log i cal re gime de ter mined by the catch ment li thol ogy, per ma frost with drawal and plant colonis ation (GoŸdzik and Konecka-Bet ley, 1992a;Forysiak et al, 2010;Kordowski et al, 2014a) are ex cep tional in this re spect. In the Pol ish Low land, sed i men ta tion of cal car e ous gyttja was caused by the li thol ogy and avail abil ity of cal car e ous ma te rial (Ca 2+ and HCO 3 ions) in the catch ment, deep en ing of de pressions oc cu pied by per ma nent wa ter bod ies, and hab i tat con ditions such as physicochemical prop er ties of the lake wa ter (Mazurek, 1990;Borówka, 1992;Apolinarska et al, 2012;Okupny et al, 2016c;Makohonienko et al, 2023). Apart from cal car e ous sed i men ta tion, an im por tant group of lac us trine depos its found in the basal parts of nu mer ous mire sec tions are de tri tal gyttja and de tri tal-clayey gyttja (¯urek and Okupny, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental reconstructions based on lake and peatland records often register changes on a regional scale, but local changes are driven by geological structure and lithology in the catchment, the morphology of the basin, the source of supply, and the catchment of surface and ground waters (Wojciechowski 2000;Błaszkiewicz 2007;Płóciennik et al 2015;Dietze et al 2016;Okupny et al 2016). Lake basins and peat bogs are important archives also of natural past geological and hydroclimatic evolution in the West Pomeranian Lake District (Jasnowski 1962;Borówka 1992;Latałowa 1992Latałowa , 1999aMalkiewicz, Tomaszewska 2009;Madeja 2012;Bloom 2015;Lamentowicz et al 2015).…”
Section: Introductionmentioning
confidence: 99%